রোমন্থন : এমসি কলেজ ষ্মরণে আমরা কজন সতীর্থ - রাকীব, মুহাম্মদ আব্দুর.; হোসেন, সৈয়দ নাজমুল.; চৌধুরী, আহমেদ মোশতাক রাজা.; চৌধুরী, পীযূষ কান্তি.; কবীর, লুৎফুল.; আল-কবির, আহমদ.; রায়, মতি লাল দেব.; আলম, রেজীনা চৌধুরী. (ঢাকা : উৎস প্রকাশন, 2022)
Collection of memoirs on Murari Chand College, Bangladesh, by its alumni.
AAL
Complimentary copy from Dr. Ahmed Mushtaque Raza Chowdhury (Former Vice Chairperson of BRAC)
Keywords: Murari Chand College -- Alumni and alumnae; Universities and colleges -- Alumni and alumnae -- Bangladesh; Universities and colleges -- Bangladesh -- Sylhet District (Bangladesh) -- Congresses; Students -- Bangladesh -- Sylhet District (Bangladesh).; Universities and colleges -- Bangladesh -- Sylhet -- History